Reformulating Government Regulation Number 39Year 2006 to Promote Integration of Development Control, Satu Data Indonesia, and National Development Risk Management - Pambudi, Andi Setyo; Prabandani, Hendra Wahanu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2025)
The governance of Indonesia’s development reflects an urgent need for a proactive control and evaluation system across the policy cycle. Previous studies have been largely technical and have not dissected the regulatory framework, leaving gaps in substance, institutional roles, and data integration. This urgency has grown following the enactment of Law Number 59 Year 2024 (RPJPN 2025–2045) and the direction of National Development Risk Management (MRPN), which demand evidence-based and risk-aware policymaking. This study analyzes the weaknesses of Government Regulation No. 39/2006, identifies the need for alignment with the new legal framework, and formulates strategic recommendations for reform. Using qualitative methods, including content and policy gap analysis, the study finds that the ex-post focus limits early detection, institutional roles and coordination remain unclear, evaluation results are not yet prerequisites for planning and budgeting, and data systems are not integrated with One Data Indonesia. Reform is needed to strengthen anticipatory controls, institutional coordination, mandatory linkage of evaluation to planning and budgeting, and interoperable digital systems. These changes are essential to ensure that evaluation becomes a responsive, adaptive, and accountable policy navigation tool. Reforming PP No. 39 Year 2006 is thus a prerequisite for accelerating the achievement of RPJPN targets and Indonesia’s broader development agenda